2012
DOI: 10.1007/s00125-012-2685-z
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine inhibits platelet–monocyte conjugation in patients with type 2 diabetes with depleted intraplatelet glutathione: a randomised controlled trial

Abstract: Aims/hypothesisThe aim of this study was to determine whether oral dosing with N-acetylcysteine (NAC) increases intraplatelet levels of the antioxidant, glutathione (GSH), and reduces platelet–monocyte conjugation in blood from patients with type 2 diabetes.MethodsIn this placebo-controlled randomised crossover study, the effect of oral NAC dosing on platelet–monocyte conjugation and intraplatelet GSH was investigated in patients with type 2 diabetes (eligibility criteria: men or post-menopausal women with wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Meanwhile, several other studies have focused on the impact of NAC on platelet function: for instance, Gibson et al demonstrated that NAC could increase intraplatelet levels of GSH, decreasing ROS levels and reducing platelet activation in vitro (98). Another study has demonstrated the antiplatelet properties of NAC in a cohort of type 2 diabetes patients (329), and showed an inhibition of monocyte-platelet conjugation, a surrogate marker of cardiovascular risk, within 2 h of administration, an effect that was maintained after daily self-administration over a 1-week period. Finally, several clinical studies and case reports have demonstrated the utility of NAC in different neuropsychiatric conditions, such as bipolar disorder (19), addiction (106,151), obsessive compulsive disorder (158), and schizophrenia (161), and as a neuroprotective agent in AD (1).…”
Section: Non-targeted Antioxidant Treatmentsmentioning
confidence: 99%
“…Meanwhile, several other studies have focused on the impact of NAC on platelet function: for instance, Gibson et al demonstrated that NAC could increase intraplatelet levels of GSH, decreasing ROS levels and reducing platelet activation in vitro (98). Another study has demonstrated the antiplatelet properties of NAC in a cohort of type 2 diabetes patients (329), and showed an inhibition of monocyte-platelet conjugation, a surrogate marker of cardiovascular risk, within 2 h of administration, an effect that was maintained after daily self-administration over a 1-week period. Finally, several clinical studies and case reports have demonstrated the utility of NAC in different neuropsychiatric conditions, such as bipolar disorder (19), addiction (106,151), obsessive compulsive disorder (158), and schizophrenia (161), and as a neuroprotective agent in AD (1).…”
Section: Non-targeted Antioxidant Treatmentsmentioning
confidence: 99%
“…Free L-cysteine, however, exhibits toxicity [13] so compound forms of L-cysteine that allow for a regulated release into cells to drive GSH biosynthesis without toxic side effects are desirable. Prodrugs of L-cysteine, such as N-acetylcysteine (NAC), have proven to be effective at increasing GSH levels when given at high doses in humans (around 1.0 g/kg body weight) [14,15]. However, side effects have been reported by patients treated with NAC suggesting that NAC releases L-cysteine at a level that can be toxic [16].…”
Section: Introductionmentioning
confidence: 98%
“…It is possible that in diabetic patients with better controlled glycemia, NAC supplementation at the current dosage could be more effective in quenching the oxidative load and an improvement in the GSH ratio might be observed. Although NAC is well known to increase the in-vivo GSH content, most studies in the literature only report the total or free GSH content and did not examine the GSH ratio [24,31,32,38,42,43]. In addition, our study provides novel information on how the free GSH content within each immune cell population responds to oral NAC supplementation, with the granulocytes being the most responsive, and T cells the least.…”
Section: Discussionmentioning
confidence: 78%
“…Previous clinical studies have examined the potential of NAC as a therapeutic agent in Type 2 diabetes patients for improving various clinical outcomes. Oral NAC supplementation was reported to enhance platelet-monocyte conjugation in diabetic patients [24], and reduce endothelial activation and systolic blood pressure in hypertensive patients with Type 2 diabetes [25], but to have no effect on contrast inducednephropathy in diabetes mellitus patients [26]. However, none of the reported studies have explored the effect of oral NAC supplementation on the immune response to infection in diabetic patients.…”
Section: Introductionmentioning
confidence: 96%